Economic Benefits of Adopting IFRS or US-GAAP: Have the Expected Costs of Equity Capital really decreased? - Holger Daske (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2004)
The question whether the adoption of International Financial Reporting Standards (IFRS) will result in measurable economic benefits is of special policy relevance in particular given the European Union?s decision to require the application of IFRS by listed companies from 2005/2007. In this paper, I investigate the common conjecture that internationally recognized high quality reporting standards (IAS/IFRS or US-GAAP) reduce the cost of capital of adopting firms (e.g. Levitt 1998; IASB 2002). Building on Leuz/Verrecchia (2000), I use a set of German firms which preadopted such standards before 2005, but investigate the potential economic benefits by analyzing their expected cost of equity capital utilizing and customizing available implied estimation methods (e.g. Gebhardt/Lee/Swaminathan 2001, Easton/Taylor/Shroff/Sougiannis 2002, Easton 2004). Evidence from a sample of about 13,000 HGB, 4,500 IAS/IFRS and 3,000 US-GAAP firm-month observations in the period 1993-2002 generally fails to document lower expected cost of equity capital and therefore measurable economic benefits for firms applying IAS/IFRS or US-GAAP. Accordingly, I caution to state that reporting under internationally accepted standards, per se, lowers the cost of equity capital of adopting firms.
Keywords: M41; 330; Kapitalkosten; International Financial Reporting Standards; Grundsätze ordnungsmässiger Buchführung; Einführung; Kosten-Nutzen-Analyse; Deutschland